Tinjauan Capital Expenditure Berdasarkan Prinsip-Prinsip Ekonomi Syariah - Rukayah, Yayah (STAI La Tansa Mashiro, 2025)
Capital expenditure is an important component in economic activities, both in government and companies. In the government sector, capital expenditure is used to improve infrastructure, public services, and long-term economic growth through fixed asset investments that generate social benefits. Meanwhile, in companies, capital expenditure aims to increase productivity and efficiency through the purchase of long-term assets. From an Islamic perspective, capital expenditure management must pay attention to the principles of maqashid sharia, which include ethics, blessings, and social benefits, by ensuring that investments are made in halal sectors and are oriented towards justice, transparency, and community welfare. This study is expected to provide deeper insights for economic practitioners, governments, and business actors in managing capital expenditures in accordance with sharia principles to achieve social welfare and fair and sustainable economic growth.